Sitting on a ticking bomb? A political ecological analysis of conservation conflicts in the Alto Nangaritza Valley, Ecuador - Gerique, Andrés; López, María Fernanda; Pohle, Perdita (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The Alto Nangaritza Valley in southeastern Ecuador constitutes one of the most important hotspots of biodiversity worldwide. Concerns about the exploitation of natural resources in this area have led to the creation of different types of conservation areas and policies during the last 30 years. These territorially-based conservation measures have provoked a series of conflicts between the conservation advocates and the Ecuadorian authorities on one side, and the local population who relies on the exploitation of natural resources on the other side. We analyze these conservation conflicts from a political ecological point of view, beginning with an introduction to the historical context, and then we consider the role of changing national development and spatial transformation priorities in these conflicts. Finally, in the face of the neoextractivist path that Ecuador has taken, we advocate even power relations between resource extraction and conservation policies.